HLA‐Cw6‐positive patients with psoriasis show improved response to methotrexate treatment. (17th May 2017) - West, J.; Ogston, S.; Berg, J.; Palmer, C.; Fleming, C.; Kumar, V.; Foerster, J.
Summary: It is well documented that patients with human leucocyte antigen (HLA)‐Cw6+ (type 1) psoriasis have increased severity and reduced age of onset of psoriasis. However, not much is known about any differential response of this genetic subgroup to various treatments. We set out to determine if there was any genetic association of the HLA‐Cw6 allele with the first‐line systemic treatment commonly used in psoriasis, methotrexate. A cohort of patients from Tayside in Scotland was recruited through a novel generic consenting process (GoShare); they were extensively phenotyped and analysed for an association of their HLA‐Cw6 genotype status with treatment outcomes. HLA‐Cw6+ patients showed notably improved response to methotrexate ( P = 0.05), and further analysis demonstrated an even greater response in a subcohort of the HLA‐Cw6+ patients, who did not have concomitant psoriatic arthritis ( P = 0.01). HLA‐Cw6+ patients also exhibited fewer treatment‐limiting adverse events. In addition to these findings, the methodology and primary clinical outcome phenotype, which we validate here, will greatly facilitate replication of the present results in independent cohorts.